Art for public engagement on emerging and controversial technologies: A literature review. (August 2022) - Fraaije, Aafke; van der Meij, Marjoleine G.; Kupper, Frank; Broerse, Jacqueline E. W.
Art is increasingly used to engage publics on emerging and controversial technologies, but we still know little about what works in art-based engagement and why. To investigate what art can do for public engagement, we systematically reviewed academic work published from 2000 to 2018 about the effect of art on organized public engagement. We used the dimensions of Responsible Research and Innovation as an analytical framework to identify what outcomes are achieved and what processes contribute to those outcomes. The 30 included studies showed that art mainly supported engagement by (1) reaching wider audiences, (2) fueling individual reflection, and (3) making visible how technologies come into being and interact with the world. With due consideration of the risks of instrumentalization, future research should empirically and reflexively investigate the outcomes and methodologies of art-based engagement, especially concerning collective reflection and change.